An Autoimmunogenic and Proinflammatory Profile Defined by the Gut Microbiota of Patients With Untreated Systemic Lupus Erythematosus. Issue 2 (29th December 2020) - Chen, Bei‐di; Jia, Xin‐miao; Xu, Jia‐yue; Zhao, Li‐dan; Ji, Jun‐yi; Wu, Bing‐xuan; Ma, Yue; Li, Hao; Zuo, Xiao‐xia; Pan, Wen‐you; Wang, Xiao‐han; Ye, Shuang; et al.
Abstract : Objective: Changes in gut microbiota have been linked to systemic lupus erythematosus (SLE), but knowledge is limited. Our study aimed to provide an in‐depth understanding of the contribution of gut microbiota to the immunopathogenesis of SLE. Methods: Fecal metagenomes from 117 patients with untreated SLE and 52 SLE patients posttreatment were aligned with 115 matched healthy controls and analyzed by whole‐genome profiling. For comparison, we assessed the fecal metagenome of MRL/ lpr mice. The oral microbiota origin of the gut species that existed in SLE patients was documented by single‐nucleotide polymorphism–based strain‐level analyses. Functional validation assays were performed to demonstrate the molecular mimicry of newly found microbial peptides. Results: Gut microbiota from individuals with SLE displayed significant differences in microbial composition and function compared to healthy controls. Certain species, including the Clostridium species ATCC BAA‐442 as well as Atopobium rimae, Shuttleworthia satelles, Actinomyces massiliensis, Bacteroides fragilis, and Clostridium leptum, were enriched in SLE gut microbiota and reduced after treatment. Enhanced lipopolysaccharide biosynthesis aligned with reduced branched chain amino acid biosynthesis was observed in the gut of SLE patients. The findings in mice were consistent with our findings in human subjects. Interestingly, some species with an oral microbiota origin were enriched in the gut of SLE patients. Functional validation assays demonstrated the proinflammatory capacities of some microbial peptides derived from SLE‐enriched species. Conclusion: This study provides detailed information on the microbiota of untreated patients with SLE, including their functional signatures, similarities with murine counterparts, oral origin, and the definition of autoantigen‐mimicking peptides. Our data demonstrate that microbiome‐altering approaches may offer valuable adjuvant therapies in SLE.